Einführung - Eybl, Franz M.; Fulda, Daniel; Süßmann, Johannes (Bündnisse. Politische, soziale und intellektuelle Allianzen im Jahrhundert der Aufklärung)

Bündnisse. Politische, soziale und intellektuelle Allianzen im Jahrhundert der Aufklärung

Das Mainufer von Aschaffenburg: Romantische Geschichtsinszenierung und Herrschaftslegitimation - Süßmann, Johannes (Kolossale Miniaturen. Festschrift für Gerrit Walther)
Keywords: Aschaffenburg Ludwig I. König von Bayern Gartenkunst Main Residenzschloß Villen Gärtner; Friedrich von Antikenrezeption Museen Herrschaftslegitimation Bildungsbürger

Blow your Trumpets Gabriel« – Der Heavy Metal und die Frage des Satanismus - Hansen, Christin (Kirchliche Zeitgeschichte)

Vernünftige Deutsche, chaotische Griechen? Stereotype und historisches Lernen - Hansen, Christin; Pleitner, Berit (Geschichte lernen)

Steuermoral in Westdeutschland nach dem Zweiten Weltkrieg. Eine diskursanalytische Rekonstruktion - Schönhärl, Korinna (Leviathan)
Die Klage über mangelnde Steuermoral ist in der aktuellen Medienberichterstattung omnipräsent, aber sie ist nicht neu: Bereits kurz nach dem Zweiten Weltkrieg wurde bemängelt, die Deutschen in den westlichen Besatzungszonen hinterzögen ihre Steuern. Verfiel die westdeutsche Steuermoral schon damals? Wie veränderte sie sich im Zeitraum zwischen 1945 und 1953? Nach einem kurzen Überblick über die Geschichte der interdisziplinären Steuermoralforschung und einigen methodischen Überlegungen, wie Historiker*innen die Entwicklung der Steuermoral qualitativ untersuchen können, wird im vorliegenden Aufsatz der Diskurs um das Steuerzahlen in der Nachkriegszeit analysiert. Durch die Analyse von Zeitungsberichten und Parlamentsdebatten werden drei unterschiedliche, konkurrierende Narrative identifiziert, die geeignet waren, ganz verschiedene »policy windows« zu öffnen. Die historische Untersuchung zeigt, dass Narrative über das (ehrliche) Steuerzahlen immer mit bestimmten politischen Interessen verknüpft sind - und dass sie deshalb auch im aktuellen Diskurs über das (ehrliche) Steuerzahlen sorgfältig analysiert werden sollten.
Keywords: Political Science and International Relations; Linguistics and Language; Sociology and Political Science; Language and Linguistics

Socially Responsible Investment in 19th Century Greece: A Case Study of a Swiss Banker - Schönhärl, Korinna (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Altruistically motivated investment has become the subject of economic, psychological and sociological research in recent years. The long tradition of ethical considerations concerning investment behavior has often been mentioned by historians but rarely investigated. This paper presents a case study of the 19th century philhellene banker Jean-Gabriel Eynard, who was philanthropically active in Greece, but also invested part of his capital on the emerging Greek market. Drawing on the methodological approach of the “sociology of morality”, this article examines how Eynard invested in Greece, which norms and values concerning investment behavior he articulated and how far they were comparable with the norms and values of today’s Socially Responsible Investment. What emerges is that the practices and the norms of Socially Responsible and Ethical Investment then and now are remarkably similar, while the “moral background” (G. Abend) has changed considerably in some, but not all points.
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science; History; Cultural Studies

The full range of leadership. Welche Zusammenhänge gibt es zwischen Führungsverhalten und schulischen Qualitätsindikatoren? - Bloh, Bea; van Ophyusen, Stefanie (Schulmanagement)

Forschendes Lernen in der Lehrerausbildung – Gestaltung und Erforschung des Praxissemesters - Bloh, Bea; Behrmann, Lars; Homt, Martina; van Ophuysen, Stefanie (Herausforderung Kohärenz: Praxisphasen in der universitären Lehrerbildung. Bildungswissenschaftliche und fachdidaktische Perspektiven)

Aural Worldmaking: An Introduction - Mildorf, Jarmila (CounterText)

The Irrelevance of Relevance Theory for the Study of Generic Fiction - Mildorf, Jarmila (Style)

Can Sounds Narrate? Prosody in Sound Poetry Performance - Mildorf, Jarmila (CounterText)

Ressourcenorientiertes Schreiben. Tagebücher, Skizzen und Notate in der sozio-therapeutischen Praxis. Mit einem Exkurs zum Tagebuch der Trauer von Roland Barthes - Mildorf, Jarmila; Ketteler, Daniel (Jahrbuch Literatur und Medizin)

Why Poetry Matters: Defamiliarization and Perspective in Poetry - Mildorf, Jarmila (Lyrik und Medizin)

„Der Imperativ des Nassauerns, Durchmogelns und Absahnens“: Debatten um Steuermoral in der BRD Anfang der 1980er Jahren - Schönhärl, Korinna (Geschichte in Wissenschaft und Unterricht)

Geld zurück! Internationale Finanzkontrolle in Griechenland im 19. Jahrhundert und in der Gegenwart - Schönhärl, Korinna (Grenzüberschreitende institutionalisierte Zusammenarbeit von der Antike bis zur Gegenwart)

Die Steuermoral weltweit. Eine Artikelserie in der Frankfurter Allgemeinen Zeitung in den Jahren 1963/64 - Schönhärl, Korinna (Moderner Kapitalismus. Wirtschafts- und unternehmenshistorische Beiträge)

"I don't see why I would ever want to use it": Analyzing the Usability of Popular Smartphone Password Managers - Seiler-Hwang, Sunyoung; Arias Cabarcos, Patricia; Marín, Andrés; Almenáres, Florina; Díaz Sánchez, Daniel; Becker, Christian (Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security, CCS 2019, London, UK, November 11-15, 2019)

Poster: Towards a Framework for Assessing Vulnerabilities of Brainwave Authentication Systems - Becker, Karen; Arias Cabarcos, Patricia; Habrich, Thilo; Becker, Christian (Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security, CCS 2019, London, UK, November 11-15, 2019)

A Survey on Adaptive Authentication - Arias Cabarcos, Patricia; Krupitzer, Christian; Becker, Christian (ACM Comput. Surv.)

Narrating Selves and the Literary from the Bible to Social Media (Partial Answers)

Aural Worldmaking: Audionarratological Approaches to Sound and Narrative (CounterText)

Dance, Text and Philosophy in Gertrude Stein’s ‘One Dancing’ and Roger Scruton’s Perictione in Colophon - Mildorf, Jarmila (Germanisch-Romanische Monatsschrift)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Autobiography, the Literary and the Everyday in Paul Auster's 'Report from the Interior' - Mildorf, Jarmila (Partial Answers)

Konzeptionelle, strukturelle und inhaltliche Gestaltungsaspekte des Praxissemesters an der Universität Paderborn - Herzig, Bardo; Wiethoff, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Symmetry and motion primitives in model predictive control - Flaßkamp, Kathrin; Ober-Blöbaum, Sina; Worthmann, Karl (MCSS)

Implikationen der digitalen Transformation für die didaktische Arbeit des betrieblichen Ausbildungspersonals - Gössling, Bernd; Hagemeier, Daniel; Janssen, Elmar; Sloane, Peter F. E. (Jahrestagung der DGfE-Sektion Berufs- und Wirtschaftspädagogik)

Berufsbildung 4.0 als didaktische Herausforderung : zum Umgang von Lehrkräften an berufsbildenden Schulen mit digitalisierten Arbeitswelten - Gössling, Bernd; Hagemeier, Daniel; Sloane, Peter F. E. (Zeitschrift für Berufs- und Wirtschaftspädagogik)

TLS/PKI Challenges and Certificate Pinning Techniques for IoT and M2M Secure Communications - Díaz Sánchez, Daniel; Marín López, Andrés; Almenárez Mendoza, Florina; Arias Cabarcos, Patricia; Simon Sherratt, R. (IEEE Commun. Surv. Tutorials)

DNS/DANE Collision-Based Distributed and Dynamic Authentication for Microservices in IoT - Díaz Sánchez, Daniel; Marín López, Andrés; Almenárez Mendoza, Florina; Arias Cabarcos, Patricia (Sensors)

Octave-Band Microwave Frequency Synthesizer Using Mode-Locked Laser as a Reference - Bahmanian, Meysam; Tiedau, Johannes; Silberhorn, Christine; Scheytt, Christoph (2019 International Topical Meeting on Microwave Photonics (MWP))
An octave-band voltage-controlled oscillator is phase-locked on the envelope of the pulse train from a mode-locked laser. The locking scheme employs a balanced Mach-Zehnder modulator with two photodiodes as a phase detector. The phase.locked loop has a loop bandwidth of approximately 1MHz and an in-band phase noise of approximately -135dBc/Hz at all frequencies. The integrated jitter from 1kHz to 100MHz is 21fs, 18.3fs and 13.8fs at 5.016GHz, 7.6GHz and 10.032GHz carrier frequencies, respectively. To the authors' knowledge, this is the best jitter performance reported for a PLL with MZM-based phase detection and the first reported PLL of this type featuring an octave-band frequency range.

Die Auswirkungen der Digitalisierung auf die Bedeutung beruflicher Qualifikation aus betrieblicher Sicht - Harteis, Christian; Goller, Michael; Fischer, Christoph (Beruf, Beruflichkeit, Employability)

Becoming a Nurse Aide: An Investigation of an Existing Workplace Curriculum in a Nursing Home - Goller, Michael; Steffen, Bianca; Harteis, Christian (Vocations and Learning)

Assessment of Flexibilisation Potential by Changing Energy Sources Using Monte Carlo Simulation - Dunkelberg, Heiko; Sondermann, Maximilian; Meschede, Henning; Hesselbach, Jens (Energies)
In the fight against anthropogenic climate change, the benefit of the integration of fluctuating renewable energies (wind and photovoltaics) into the electricity grid is a widely proved concept. At the same time, a fluctuating and decentralised supply of energy, especially at lower voltage levels, leads to a local discrepancy in the power balance between generation and consumption. A possible solution in connection with demand side management is the grid-oriented flexibilisation of energy demand. The present study shows how the use of an innovative hybrid-redundant high-temperature heat system (combined heat and power (CHP), power-to-heat system (PtH), gas boiler) can contribute to a flexibilisation of the electrical energy demand of plastics processing companies. In this context, the flexibilisation potential of a company is to be understood as the grid-related change of the energy supply through a change of the energy sources within the framework of the process heat supply. For this purpose, an omniscient control algorithm is developed that specifies the schedule of the individual system components. A sensitivity analysis is used to test the functionality of the control algorithm. Determination of the electrical flexibilisation potential is carried out via a comprehensive simulation study using Monte Carlo methods. For this purpose, the residual load curves of four characteristic distribution grids with a high share of renewable energies as well as heat load profiles of injection moulding machines are taken into consideration. A frequency distribution provides information on the electrical flexibilisation potential to be expected depending on the various combinations. The evaluation is carried out using a specially introduced logic, which identifies grid-relevant changes in the company's power consumption as flexibilisation potential based on a reference load curve. The results show that a reliable energy supply for production is possible despite flexibilisation. Depending on the grid under consideration, there are differences in the exploitation of the potential, which essentially depends on the installed renewable capacity. Depending on the scenario under consideration, an average of up to 1486 kWhel can be shifted in a positive direction and 1199 kWhel in a negative direction.

On the impact of probabilistic weather data on the economically optimal design of renewable energy systems – a case study on La Gomera island - Meschede, Henning; Hesselbach, Jens; Child, Michael; Breyer, Christian (International Journal of Sustainable Energy Planning and Management)
Renewable energy and storage systems are widely discussed to minimise the impact of global warming. In addition to the temporal resolution of simulation tools, also the chosen input data might have a strong impact on the performance of renewable energy systems, and energy storage systems in particular. This study analyses the impact of probabilistic weather data on the design of renewable energy systems. The main objective is hereby the determination of the robustness of a recently state-of-the-art design process of a 100% renewable energy and storage system with varying probabilistic input data. The island of La Gomera, Canary Islands, is taken as a case study. Although all analysed systems show some variance in their results, the combination of vehicle-to-grid and power-to-hydrogen shows the best economic performance. Hereby, small island energy systems depending heavily on wind energy show higher variations than those with high shares of solar energy. This analysis illustrates clearly that the choice of one historical reference year is not suitable to determine the expected performance of an energy system. To learn about their sensitivity, synthetic probabilistic inputs as applied in this study are a good way to determine both the expected mean values and their variance.

Classification and clustering of the German plastic industry with a special focus on the implementation of low and high temperature waste heat - Dunkelberg, Heiko; Schlosser, Florian; Veitengruber, Frank; Meschede, Henning; Heidrich, Tobias (Journal of Cleaner Production)

On the transferability of smart energy systems on off-grid islands using cluster analysis – A case study for the Philippine archipelago - Meschede, Henning; Esparcia, Eugene A.; Holzapfel, Peter; Bertheau, Paul; Ang, Rosario C.; Blanco, Ariel C.; Ocon, Joey D. (Applied Energy)

Automatic Time Series Segmentation as the Basis for Unsupervised, Non-Intrusive Load Monitoring of Machine Tools - Seevers, J-P.; Johst, J.; Weiß, T.; Meschede, Henning; Hesselbach, J. (Procedia CIRP)

Increased utilisation of renewable energies through demand response in the water supply sector – A case study - Meschede, Henning (Energy)

Unraveling the Search Space of Abusive Language in Wikipedia with Dynamic Lexicon Acquisition - Chen, Wei-Fan; Al-Khatib, Khalid; Hagen, Matthias; Wachsmuth, Henning; Stein, Benno (Proceedings of the Second Workshop on Natural Language Processing for Internet Freedom)

Profile der Gegenwartsliteratur (Herausgebertätigkeit von Norbert Otto Eke ab Bd. 1, 2019)
Bd. 1: Michael Hofmann, Klaus von Stosch und Swen Schulte Eickholt. Würzburg 2019. 271 S.

A Hybrid Space Compactor for Adaptive X-Handling - Maaz, Mohammad Urf; Sprenger, Alexander; Hellebrand, Sybille (50th IEEE International Test Conference (ITC))
The test for small delay faults is of major importance for predicting potential early life failures or wearout problems. Typically, a faster-than-at-speed test (FAST) with sev¬eral different frequencies is used to detect also hidden small delays, which can only be propagated over short paths. But then the outputs at the end of long paths may no longer reach their stable values at the nominal observation time and must be considered as unknown (X-values). Thus, test response compaction for FAST must be extremely flexible to cope with high X-rates, which also vary with the test frequencies. Stochastic compaction introduced by Mitra et al. is controlled by weighted pseudo-random signals allowing for easy adaptation to varying conditions. As demonstrated in previous work, the pseudo-random control can be optimized for high fault efficiency or X-reduction, but a given target in fault efficiency cannot be guaranteed. To close this gap, a hybrid space compactor is introduced in this paper. It is based on the observation that many faults are lost in the compaction of relatively few critical test patterns. For these critical patterns a deterministic compaction phase is added to the test, where the existing compactor structure is re-used, but controlled by specifically determined control vectors.
Keywords: Faster-than-at-speed test; BIST; DFT; Test response compaction; Stochastic compactor; X-handling

Wärmeübertragung in Mikrokanälen zur Anwendung in neuartigen Wärmemotoren - Mügge, Nils; Kenig, Eugeny (Wärmeübertragung mit Phasenwechsel in fluiden Systemen: Ein Update)

Wärmegetriebene Motoren - Glouchenkov, Maxim; Kronberg, Alexander; Kenig, Eugeny; Mügge, Nils (CITplus)

Rauschen, Klang und Stille. Zur Musikalität von Literatur am Beispiel von Rilkes Malte Laurids Brigge. - van Laak, Lothar (Rilkes Musikalität)

„Profile der Gegenwartsliteratur“

Literarische Institutionen (Reihe: Grundthemen der Literaturwissenschaft)

"In erster Linie Kopfsache"!? ‒ Einstellungen zu schulischer Inklusion von Lehrkräften und Lehramtsstudierenden: Theoretische Grundlagen und jüngere empirische Befunde - Kullmann, Harry; Hülshoff, Andreas (Zwischen Persönlichkeitsbildung und Leistungsentwicklung. Fachspezifische Zugänge zu inklusivem Unterricht im interdisziplinären Diskurs)

Inklusion im schulischen Alltag – Praxiskonzepte und Forschungsergebnisse aus der Laborschule Bielefeld

Dem Verstehen auf der Spur – ausgewählte Befunde zu den Grundvorstellungen von Schülerinnen und Schülern beim Rechnen mit negativen Zahlen aus einem Unterrichtsstudien-Projekt zum inklusiven Mathematikunterricht - Kullmann, Harry; Friedli, Reto; Hattermann, Mathias (Inklusion im schulischen Alltag – Praxiskonzepte und Forschungsergebnisse aus der Laborschule)

Subjektive Wahrnehmung von Inklusion durch Schülerinnen und Schüler - Geist, Sabine; Kullmann, Harry; Lütje-Klose, Birgit; Siepmann, Christof (Inklusion im schulischen Alltag – Praxiskonzepte und Forschungsergebnisse aus der Laborschule)

Improved fractal Weyl bounds for hyperbolic manifolds. With an appendix by David Borthwick, Semyon Dyatlov and Tobias Weich - Dyatlov, Semyon; Borthwick, David; Weich, Tobias (Journal of the European Mathematical Society)
Keywords: Applied Mathematics; General Mathematics

Rezension: Klaus Volkert: In höheren Räumen – Der Weg der Geometrie in die vierte Dimension - Hoffmann, Max (Mathematische Semesterberichte)

II. Historischer Abriss: 1. Frühe Hochkulturen bis Europa des 17. Jahrhunderts - Elit, Stefan (Literarische Institutionen (Grundthemen der Literaturwissenschaft))

Spectral Asymptotics for Kinetic Brownian Motion on Hyperbolic Surfaces - Kolb, Martin; Weich, Tobias; Wolf, Lasse Lennart (arXiv:1909.06183)
The kinetic Brownian motion on the sphere bundle of a Riemannian manifold $M$ is a stochastic process that models a random perturbation of the geodesic flow. If $M$ is a orientable compact constant negatively curved surface, we show that in the limit of infinitely large perturbation the $L^2$-spectrum of the infinitesimal generator of a time rescaled version of the process converges to the Laplace spectrum of the base manifold. In addition, we give explicit error estimates for the convergence to equilibrium. The proofs are based on noncommutative harmonic analysis of $SL_2(\mathbb{R})$.

Michael Ostheimer: Leseland. Chronotopographie der DDR- und Post-DDR-Literatur, Göttingen 2018 - Elit, Stefan (Arbitrium 37, H. 2)

Zwischen den Sprachen – mit der Sprache? Deutschsprachige Literatur in Palästina und Israel - Eke, Norbert Otto; Willeke, Stephanie (Zwischen den Sprachen – mit der Sprache? Deutschsprachige Literatur in Palästina und Israel)

„Einmal furchtlos vor Menschen sein und kühn!“ Max Zweigs Arbeit am Gründungsmythos Israels - Eke, Norbert Otto (Zwischen den Sprachen – mit der Sprache? Deutschsprachige Literatur in Palästina und Israel)

Schmerz und Ironie. Mascha Kaléko und die deutsche Kultur (mit Blick auf Heinrich Heine) - van Laak, Lothar (Zwischen den Sprachen - mit der Sprache?)

Zwischen den Sprachen – mit der Sprache? Deutschsprachige Literatur in Palästina und Israel

"Victorian Values in Nineteenth- and Twenty-First-Century Advertising and Consumer Practices" - Strauß, Sara (Victorian Ideologies in Contemporary British Cultures)

"Silvia Pellicer-Ortín, Julia Tofantšuk (eds.), Women on the Move. Body, Memory and Femininity in Present-Day Transnational Diasporic Writing" - Strauß, Sara (Miranda: Multidisciplinary Peer-Reviewed Journal on the English-Speaking World)

Portfolioarbeit im Kontext von Sprachenunterricht. Neue internationale Entwicklungen

Schreibprozesse unterstützen: Der Einsatz von Portfolios und Schreibberatung im DaF- und DaZ-Unterricht - Ballweg, Sandra (Produktion und Partizipation in Deutsch als Fremd- und Zweitsprache: Sprechen - Schreiben - Mitreden. Dokumentation der siebten Gesamtschweizerischen Tagung für Deutschlehrerinnen und Deutschlehrer)

Portfolio im Kontext von Mehrsprachigkeit - Ballweg, Sandra (Handbuch Mehrsprachigkeits- und Mehrkulturalitätsdidaktik)

Erst-, Zweit- und Mehrsprachenerwerb - Ballweg, Sandra (Handbuch Mehrsprachigkeits- und Mehrkulturalitätsdidaktik)

Die Ethik der Widersetzlichkeit. Theoretische und literarische Transformationen der Antigone, Berlin u.a.: Peter Lang (Historisch-kritische Arbeiten zur deutschen Literatur) - Böker, Ines

Schnelles inhaltliches Feedback zu Entwürfen - Scharlau, Ingrid; Heuer, Claudia (Wissenschaftliches Lesen und Schreiben vermitteln)

Psychological Feasibility of a Virtual Cycling Environment for Human-in-the-Loop Experiments - Stratmann, Lukas; Buse, Dominik S.; Heinovski, Julian; Klingler, Florian; Sommer, Christoph; Tünnermann, Jan; Scharlau, Ingrid; Dressler, Falko (INFORMATIK 2019: 50 Jahre Gesellschaft für Informatik – Informatik für Gesellschaft (Workshop-Beiträge))

Plunging into a world? A novel approach to undergraduates’ metaphors of reading - Scharlau, Ingrid; Körber, Miriam; Karsten, Andrea (Frontline Learning Research)
Although there is considerable research on and knowledge about students’ conceptual-izations of learning or academic practices and skills, the variability of these conceptu-alizations has been consistently neglected.In the present study, we address this varia-bility in the field of academic readingwith the help of a novel approach. Drawing on qualitative metaphor analysis, we report a detailed system of students’ conceptual met-aphors of reading. Ourspecific methodologicalapproach to identify the structure of these conceptual metaphorsallowsto analyze subjective agency on a lexical as well as grammatical level.The conceptual metaphors we identified by this method are markedly variable, although they create an overall impression of medium to low agency, that is a reader who is only weakly active or potent. Interrater reliability of the coding system was very good. We also report and analyze the frequency of the conceptual metaphors ina sample of 143 texts written by bachelor students.
Keywords: metaphor; conceptual metaphor; metaphor analysis; academic reading; transitivity

Welche Rolle spielen Fachkulturen heute? Bericht von einer Erkundungsstudie. - Scharlau, Ingrid; Huber, Ludwig (die hochschullehre)
With the present exploration, we aimed to answer the question whether distinct disciplinary cultures are present at today’s universities. To this purpose, we conducted 16 interviews with scholars from different disciplines. Qualitative analysis shows that disciplinary cultures in a narrow, epistemological sense (including forms of knowledge and work as well as organisation of teaching and learning) are perceived as distinct aspects of higher education and deemed important. Disciplinary cultures in a broader sense related to lifestyle and habitus, however, were hardly reported and not perceived as characteristic. Questions of social selectivity or inequality within universities were rarely touched in the interviews. Own cultures are typically described as rather heterogeneous, which is not the case for other cultures. Handling of possible cultures as well as differences by the interviewees turned out to be very cautious, at the same time restrained and respectful. Even where differences are observed or different values are revealed, there is little evidence of disputes. Consequences of these findings for research into disciplinary cultures and higher education are discussed.
Keywords: disciplinary culture; habitus; distinctions

.... und wenn etwas unglaubwürdig klingt, was man ihnen nachsagt, so könnt ihr versichert sein, daß es noch um die Hälfte hinter der Wahrheit zurückbleibt - Markewitz, Friedrich (Zeitschrift für Angewandte Linguistik,)

Thermographic phosphor heat flux measurements of laminar methane/air flame impinging on a cylindrical surface - Oketch, Peter Obara; Gonchikzhapov, Munko; Bergmann, Ulf; Atakan, Burak (Measurement Science and Technology)
Abstract The stagnation point heat fluxes of methane/air flames impinging normal on a cylindrical surface were determined experimentally. Light induced phosphorescence from thermographic phosphors was used to investigate surface temperatures at the stagnation point from a nearly 1D laminar premixed flame burning against a water-cooled ceramic tube. The ceramic tube was coated with 1.1% chromium-doped alumina (ruby) at the impingement area and excited with a green light-emitting diode (LED) to measure the surface temperature. The flame temperature profiles were also measured with a thermocouple of type R (Pt/Pt + 13% Rh). Effects on variations in cold gas velocity (0.1 m s −1 –0.5 m s −1 ) relative to the flame speed, equivalence ratio (Ф = 0.85–1.2), burner to impingement surface spacing ( H / d = 0.5–2) and surface curvature are reported. The stagnation point heat fluxes are strongly influenced by the flame stabilization mechanism, which changes from burner to wall stabilization, which also is seen from the measured flame temperature profiles. Increasing the cold gas velocity of the reactants leads to higher stagnation point heat fluxes. In addition, decreasing the distance between the burner and impingement surface increases the heat flux, with higher heat fluxes recorded for a tube compared to a flat plate.
Keywords: Applied Mathematics; Instrumentation; Engineering (miscellaneous)

Experimental and numerical study of polyoxymethylene (Aldrich) combustion in counterflow - Glaznev, Roman K.; Karpov, Alexander I.; Korobeinichev, Oleg P.; Bolkisev, Andrei A.; Shaklein, Artem A.; Shmakov, Andrey G.; Paletsky, Alexander A.; Gonchikzhapov, Munko B.; Kumar, Amit (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Handbuch Text und Gespräch - Markewitz, Friedrich (Gesprächsforschung – Online Zeitschrift zur verbalen Interaktion)

Fachsprachen. Die Konstruktion von Welten - Markewitz, Friedrich (Zeitschrift für Rezensionen zur germanistischen Sprachwissenschaft)

Grundlagen und Paradigmen einer systemtheoretisch fundierten Textsortenlinguistik – Eine kritische Bestandsaufnahme - Markewitz, Friedrich (Zeitschrift für Literaturwissenschaft und Literatur (LiLi))

The Effect of Marker-less Augmented Reality on Task and Learning Performance - Sommerauer, Peter; Müller, Oliver; Maxim, Leonard; Østman, Nils (International Conference on Wirtschaftsinformatik)
Augmented Reality (AR) technologies have evolved rapidly over the last years, particularly with regard to user interfaces, input devices, and cameras used in mobile devices for object and gesture recognition. While early AR systems relied on pre-defined trigger images or QR code markers, modern AR applications leverage machine learning techniques to identify objects in their physical environments. So far, only few empirical studies have investigated AR's potential for supporting learning and task assistance using such marker-less AR. In order to address this research gap, we implemented an AR application (app)with the aim to analyze the effectiveness of marker-less AR applied in a mundane setting which can be used for on-the-job training and more formal educational settings. The results of our laboratory experiment show that while participants working with AR needed significantly more time to fulfill the given task, the participants who were supported by AR learned significantly more.

Fostering pre-service economics teachers´ reflection on their attitudes towards the discipline - Jenert, Tobias; Brahm , Taiga

Pirates – The Young and the Jobless: The Effect of Youth Bulges and Youth Labor Market Integration on Maritime Piracy - Gries, Thomas; Redlin, Margarete (Defence and Peace Economics)

Intergenerationelle Beziehungen in der Familie - Buhl, Heike M.; Sommer, Sabrina (Psychotherapie im Alter)
Beziehungen zwischen Erwachsenen und ihren Eltern sind durch Interdependenzen und Dependenzen gekennzeichnet. Während das Zusammenleben von Familien mit Kindern im mittleren Erwachsenenalter dabei ganz überwiegend durch Interdependenz geprägt ist, nehmen im Alter Dependenzen durch gesundheitliche Beeinträchtigungen der Eltern zu. Mit Blick darauf werden im Artikel behaviorale, kognitive und emotionale Merkmale von Eltern-Kind-Beziehungen erläutert und theoretisch in zentrale Konzepte eingebettet. Das Verhalten ist durch Solidarität zwischen den Generationen, aber auch durch Aspekte des Einflusses innerhalb der Beziehung und aufeinander, gekennzeichnet. Um Familienkognitionen zu beschreiben, werden die verwandten Konzepte der Individuation und der filialen Reife herangezogen. Verhalten, wie auch Kognitionen, sind eng mit dem dritten Beziehungsmerkmal, der Affektivität verknüpft, das neben positiven auch negative Gefühle sowie Ambivalenzen umfasst.

Feedback in internet-based self-assessments and its effects on acceptance and motivation - Bohndick, Carla; Menne, Christina; Kohlmeyer, Susanne; Buhl, Heike M. (Journal of Further and Higher Education)
Internet-based self-assessments (ISAs) are tools used to support finding the right educational fit for higher education (HE) students. ISAs typically consist of a questionnaire followed by a feedback report about the results. It is unknown how the characteristics of the feedback report itself affect individuals’ acceptance and motivation to follow the advice from the report. Literature on feedback in general has suggested relationships between acceptance of feedback and motivation, feedback sign (positive versus negative) and regulatory focus (promotion focus versus prevention focus), influence acceptance and the motivation to develop. To investigate if these findings are transferable to the context of ISAs, we conducted an online study with N = 249 German university students (73% female; M = 22.84 years of age (SD = 3.73)) and a bogus self-assessment. Feedback sign was manipulated randomly, and the regulatory focus was measured by values. Regression analyses indicate a positive effect of positive feedback sign, but no differences regarding regulatory focus.

Bedingungen elterlichen Unterstützungsverhaltens beim Lesen im Grundschulalter. Eine Untersuchung relevanter Prozessmerkmale - Hilkenmeier, Johanna; Wiescholek, Sabrina; Buhl, Heike M. (Zeitschrift für Soziologie der Erziehung und Sozialisation)

Anstoß und Unterstützung der professionellen Weiterentwicklung im Lehramtstudium durch weiterentwicklungsorientiertes Online-Self-Assessment - Bohndick, Carla; Kohlmeyer, Susanne; Buhl, Heike M. (Lehrerbildung auf dem Prüfstand)

Fit für Inklusion - Entwicklung und Validierung einer deutschsprachigen Kurzskala zum Umgang mit Heterogenität - Kohlmeyer, Susanne; Buhl, Heike M.; Bonanati, Sabrina; Dannowsky, Janika; Bohndick, Carla (Empirische Pädagogik)

Das Elterngespräch aus Forschungsperspektive. Strategien zur Förderung elterlichen Engagements - Hilkenmeier, Johanna; Greiner, Christian; Buhl, Heike M. (SCHULE inklusiv)

A DC bias approach to the characterisation of non-linear material parameters of piezoelectric ceramics - Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd
Keywords: piezoelectric materials; piezoelectric properties; DC bias field; non-linear material parameters

Arbitrary sensitivity for inverse problems in piezoelectricity - Jurgelucks, Benjamin; Schulze, Veronika; Feldmann, Nadine; Claes, Leander

Genericity in Network Dynamics - Schwenker, Sören
This thesis deals with the investigation of dynamical properties – in particular generic synchrony breaking bifurcations – that are inherent to the structure of a semigroup network as well the numerous algebraic structures that are related to these types of networks. Most notably we investigate the interplay between network dynamics and monoid representation theory as induced by the fundamental network construction in terms of hidden symmetry as introduced by RINK and SANDERS. After providing a brief survey of the field of network dynamics in Part I, we thoroughly introduce the formalism of semigroup networks, the customized dynamical systems theory, and the necessary background from monoid representation theory in Chapters 3 and 4. The remainder of Part II investigates generic synchrony breaking bifurcations and contains three major results. The first is Theorem 5.11, which shows that generic symmetry breaking steady state bifurcations in monoid equivariant dynamics occur along absolutely indecomposable subrepresentations – a natural generalization of the corresponding statement for group equivariant dynamics. Then Theorem 7.12 relates the decomposition of a representation given by a network with high-dimensional internal phase spaces to that induced by the same network with one-dimensional internal phase spaces. This result is used to show that there is a smallest dimension of internal dynamics in which all generic l-parameter bifurcations of a fundamental network can be observed (Theorem 7.24). In Part III, we employ the machinery that was summarized and further developed in Part II to feedforward networks. We propose a general definition of this structural feature of a network and show that it can equivalently be characterized in different algebraic notions in Theorem 8.35. These are then exploited to fully classify the corresponding monoid representation for any feedforward network and to classify generic synchrony breaking steady state bifurcations with one- or highdimensional internal dynamics.

Stochastic Spikes and Poisson Approximation of One-Dimensional Stochastic Differential Equations with Applications to Continuously Measured Quantum Systems - Kolb, Martin; Liesenfeld, Matthias (Annales Henri Poincaré)
Motivated by the recent contribution (Bauer and Bernard in Annales Henri Poincaré 19:653–693, 2018), we study the scaling limit behavior of a class of one-dimensional stochastic differential equations which has a unique attracting point subject to a small additional repulsive perturbation. Problems of this type appear in the analysis of continuously monitored quantum systems. We extend the results of Bauer and Bernard (Annales Henri Poincaré 19:653–693, 2018) and prove a general result concerning the convergence to a homogeneous Poisson process using only classical probabilistic tools.

Theoretical properties of quasi-stationary Monte Carlo methods - Wang, Andi Q.; Kolb, Martin; Roberts, Gareth O.; Steinsaltz, David (The Annals of Applied Probability)

Quasistationary distributions for one-dimensional diffusions with two singular boundary points - Hening, Alexandru; Kolb, Martin (Stochastic Processes and their Applications)
In the present work we characterize the existence of quasistationary distributions for diffusions on (0,∞) allowing singular behavior at 0 and ∞. If absorption at 0 is certain, we show that there exists a quasistationary distribution as soon as the spectrum of the generator is strictly positive. This complements results of Collet et al. and Kolb/Steinsaltz for 0 being a regular boundary point and extends results by Collet et al. on singular diffusions. We also study the existence and uniqueness of quasistationary distributions for a class of one-dimensional diffusions with killing that arise from a biological example and which have two inaccessible boundary points (more specifically 0 is natural and ∞ is entrance).

Feuilletons als Bildarchive historischen Wissens. Städteminiaturen der Weimarer Republik - Öhlschläger, Claudia (KulturPoetik, Heft 2)

Vitamin D and the Risk of Depression: A Causal Relationship? Findings from a Mendelian Randomization Study - Libuda, Lars; Laabs, Björn-Hergen; Ludwig, Christine; Bühlmeier, Judith; Antel, Jochen; Hinney, Anke; Naaresh, Roaa; Föcker, Manuel; Hebebrand, Johannes; König, Inke R.; Peters, Triinu (Nutrients)
While observational studies show an association between 25(OH)vitamin D concentrations and depressive symptoms, intervention studies, which examine the preventive effects of vitamin D supplementation on the development of depression, are lacking. To estimate the role of lowered 25(OH)vitamin D concentrations in the etiology of depressive disorders, we conducted a two-sample Mendelian randomization (MR) study on depression, i.e., “depressive symptoms” (DS, n = 161,460) and “broad depression” (BD, n = 113,769 cases and 208,811 controls). Six single nucleotide polymorphisms (SNPs), which were genome-wide significantly associated with 25(OH)vitamin D concentrations in 79,366 subjects from the SUNLIGHT genome-wide association study (GWAS), were used as an instrumental variable. None of the six SNPs was associated with DS or BD (all p > 0.05). MR analysis revealed no causal effects of 25(OH)vitamin D concentration, either on DS (inverse variance weighted (IVW); b = 0.025, SE = 0.038, p = 0.52) or on BD (IVW; b = 0.020, SE = 0.012, p = 0.10). Sensitivity analyses confirmed that 25(OH)vitamin D concentrations were not significantly associated with DS or BD. The findings from this MR study indicate no causal relationship between vitamin D concentrations and depressive symptoms, or broad depression. Conflicting findings from observational studies might have resulted from residual confounding or reverse causation.

Risk factors for a low weight gain in the early stage of adolescent anorexia nervosa inpatient treatment: findings from a pilot study - Knoll-Pientka, Nadja; Bühlmeier, Judith; Peters, Triinu; Albrecht, Muriel; Adams, Frederike; Wustrau, Katharina; Teufel, Martin; Hebebrand, Johannes; Föcker, Manuel; Libuda, Lars (Eating and Weight Disorders - Studies on Anorexia, Bulimia and Obesity)

Clinical Trials Required to Assess Potential Benefits and Side Effects of Treatment of Patients With Anorexia Nervosa With Recombinant Human Leptin - Hebebrand, Johannes; Milos, Gabriella; Wabitsch, Martin; Teufel, Martin; Führer, Dagmar; Bühlmeier, Judith; Libuda, Lars; Ludwig, Christine; Antel, Jochen (Frontiers in Psychology)

Retrospektive Evaluation der Umsetzung einer klinikinternen Handlungsanweisung zur Ernährungstherapie von Intensivpatienten - Dresen, Ellen; Weißbrich, Carsten; Bühlmeier, Judith; Weisheit, Christina; Egert, Sarah; Putensen, Christian; Stehle, Peter (Aktuelle Ernährungsmedizin)
Zusammenfassung Hintergrund Die begleitende Ernährungstherapie von Intensivpatienten stellt eine besondere Herausforderung in der klinischen Routine dar und erfordert die Implementation von leitlinienbasierten Handlungsanweisungen. Methoden In einer retrospektiven Analyse wurde die Umsetzung der klinikinternen Handlungsanweisung zur Ernährung kritisch kranker Patienten (Gültigkeitszeitraum September 2013 bis Januar 2016) sowie der Anordnung zur Ernährungstherapie auf einer operativen Intensivstation des Universitätsklinikums Bonn an Daten des Ernährungsmanagements von 31 Langzeit-Intensivpatienten (7 Frauen; Alter: 60 ± 17 Jahre; BMI: 28 ± 10 kg/m2; Dauer des Intensivaufenthalts: 34 ± 16 Tage) evaluiert. Ausgewertet wurden Daten zur Initiation, zum Ablauf sowie zur Berechnung und Umsetzung der Energie- und Proteinzufuhr. Dazu wurden jeweils die im Stationsalltag angeordnete bzw. protokollierte Zufuhr, die protokollierte Zufuhr abzüglich Reflux sowie das retrospektiv beurteilte Ziel, welches durch die klinikinterne Handlungsanweisung indiziert war, miteinander verglichen (linear gemischtes Modell). Ergebnisse Mit der enteralen Ernährung wurde im Mittel an Tag 4 ± 3, mit der (supplementierenden) parenteralen an Tag 3 ± 3 begonnen. Die Energiezufuhr wurde mit Korrekturfaktoren als ein Vielfaches des Grundumsatzes nach Harris & Benedict berechnet. Der individuell verwendete Korrekturfaktor zur Berechnung der angeordneten Energiezufuhr wich über die gesamte Dauer des stationären Aufenthalts 0,1 ± 0,3 vom retrospektiv als angemessen erachteten Korrekturfaktor ab. Hieraus resultierte eine Abweichung der angeordneten Energiezufuhr vom Energieziel von 123 ± 528 kcal/24 h. Insbesondere in den Tagen 1 – 10 betrug die Abweichung des angeordneten vom retrospektiv als angemessen erachteten Korrekturfaktor 0,2 ± 0,4, was zu einer Differenz zwischen angeordneter Energiezufuhr und Energieziel von 426 ± 772 kcal/24 h führte. Die protokollierte Proteinzufuhr lag über die gesamte Behandlungsdauer bei 1,1 g/kg KG/24 h, während das retrospektiv ermittelte Proteinziel 1,0 g/kg KG/24 h betrug. Schlussfolgerung Die Analyse liefert vertrauenswürdige Daten zur Implementation einer individualisierten Ernährungstherapie von Langzeit-Intensivpatienten auf einer operativen Intensivstation; diese können zur Weiterentwicklung von entsprechenden Handlungsanweisungen genutzt werden. Defizite bestehen sowohl im zeitlichen Ablauf (zu später Beginn) als auch in der Anordnung der Energie-/Nährstoffzufuhr. Umfassende Schulungen des ärztlichen und pflegerischen Personals zur Anwendung/Umsetzung der Ernährungstherapie sind zu empfehlen.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Ansichtspostkarte - Öhlschläger, Claudia (Enzyklopädie der kleinen Formen [Audio-Enzyklopädie des Podcasts microform], URL: www.kleine-formen.de/enzyklopaedie-ansichtspostkarte)

Georges de Scudéry et le théâtre - Schlieper, Hendrik; Steigerwald, Jörn (Papers on French Seventeenth Century Literature, 91)